Hospital teaching status and trascatheter aortic valve replacement outcomes in the United States: Analysis of the national inpatient sample. Issue 7 (10th August 2017) - Telila, Tesfaye; Akintoye, Emmanuel; Ando, Tomo; Merid, Obsinet; Palla, Mohan; Mallikethi‐Reddy, Sagar; Briasoulis, Alexandros; Grines, Cindy; Afonso, Luis
Abstract: Background: Evidence suggests that medical service offerings vary by hospital teaching status. However, little is known about how these translate to patient outcomes. We therefore sought to evaluate this gap in knowledge in patients undergoing Transcatheter aortic valve replacement (TAVR) in the United States. Methods: This study was conducted using the National Inpatient Sample (NIS) in the United States from 2011 to 2014. Teaching status was classified, as teaching vs. nonteaching and endpoints were clinical outcomes, length of stay and cost. Procedure‐related complications were identified via ICD‐9 coding and analysis was performed via mixed effect model. Results: An estimated 33, 790 TAVR procedures were performed in the U.S between 2011 and 2014, out of which 89.3% were in teaching hospitals. Mean (SD) age was 81.4 (8.5) and 47% were females. There was no significant difference between teaching versus nonteaching hospitals in regards to the primary outcome of in‐hospital mortality and secondary outcomes of several cardiovascular and other end points except for a high rates of acute kidney injury (AKI) (OR: 1.34 [95% CI, 1.04–1.72]) and lower rate for use of mechanical circulatory support devices in teaching vs. nonteaching centers. The mean length of stay was significantly higher in teaching hospitals (7.7 days) vs. nonteaching hospitals (6.8 days) ( P  = 0.002) and so was the median cost of hospitalization (USD 50, 814 vs. USD 48, 787, P  = 0.02) for teaching vs. nonteaching centers. Conclusion: Most TAVR related short‐term outcomes including all cause in‐hospital mortality are about the same in teaching and nonteaching hospitals. However, AKI, length of hospital stay and TAVR related cost were significantly higher in teaching than nonteaching hospitals. There was more use of mechanical circulatory support in nonteaching than teaching hospitals.